2022
DOI: 10.1371/journal.pone.0275602
|View full text |Cite
|
Sign up to set email alerts
|

Wound healing in db/db mice with type 2 diabetes using non-contact exposure with an argon non-thermal atmospheric pressure plasma jet device

Abstract: A non-thermal atmospheric pressure plasma jet (APPJ) may stimulate cells and tissues or result in cell death depending on the intensity of plasma at the target; therefore, we herein investigated the effects of non-thermal plasma under non-contact conditions on the healing of full-thickness wounds in diabetic mice (DM+ group) and normal mice (DM- group). A hydrogen peroxide colorimetric method and high performance liquid chromatography showed that APPJ produced low amounts of reactive oxygen and nitrogen specie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…Iswara et al. reported that the body weight of non-diabetic mouse model does not change after wound injury, whereas that of diabetic mouse model decreases after wound injury [ 36 ]. We hypothesize that this weight loss may be related to hyperglycemia and impaired blood flow in the third-degree burn diabetic mouse model.…”
Section: Discussionmentioning
confidence: 99%
“…Iswara et al. reported that the body weight of non-diabetic mouse model does not change after wound injury, whereas that of diabetic mouse model decreases after wound injury [ 36 ]. We hypothesize that this weight loss may be related to hyperglycemia and impaired blood flow in the third-degree burn diabetic mouse model.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, a critical issue to the success the social implementation of plasma irradiation to seeds is to determine the health effects and composition of the harvested crops from the plasma-irradiated seeds. However, as far as the authors know, there are no reports in which the health effects on other organisms and composition of harvested crops from plasma-irradiated seeds have been investigated, despite the various clinical trials for the medical application of plasma [26][27][28][29][30][31] . Thus, this study aimed to evaluate fundamental information on the composition and health effects of a crop cultivated from plasma-irradiated seeds.…”
mentioning
confidence: 99%